2017
DOI: 10.1016/j.ijppaw.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate hosts: Hunting dogs and recolonizing grey wolves share their endoparasites

Abstract: Understanding how closely related wildlife species and their domesticated counterparts exchange or share parasites, or replace each other in parasite life cycles, is of great interest to veterinary and human public health, and wildlife ecology. Grey wolves (Canis lupus) host and spread endoparasites that can either directly infect canid conspecifics or their prey serving as intermediate hosts of indirectly transmitted species. The wolf recolonization of Central Europe represents an opportunity to study parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
(92 reference statements)
2
12
1
Order By: Relevance
“…Other authors reported the presence of Ancylostomidae gen. sp. (Ancylostoma/Uncinaria) between 2% and 45.7% [22,24]. Similar data have been published by other authors in Spain and Europe regarding the prevalence of Trichuris vulpis [25], except those from Balmori et al [26] in the Cantabrian Mountains (42.9%).…”
Section: Discussionsupporting
confidence: 77%
“…Other authors reported the presence of Ancylostomidae gen. sp. (Ancylostoma/Uncinaria) between 2% and 45.7% [22,24]. Similar data have been published by other authors in Spain and Europe regarding the prevalence of Trichuris vulpis [25], except those from Balmori et al [26] in the Cantabrian Mountains (42.9%).…”
Section: Discussionsupporting
confidence: 77%
“…faeces or vomitus). When parasites are shared by sympatric host species, entire communities might be affected (Holt and Dobson, 2007) and grey wolves ( Canis lupus ) living in sympatry with large, reservoir populations of dogs ( Canis familiaris ) are at a higher risk of infection (Murray et al, 1999; Randall et al, 2004; Cleaveland et al, 2007; Lesniak et al, 2017b). Close physical contact between group members is characteristic of social canids such as wolves and greatly enhances within-pack transmission of pathogens (Johnson et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A recent comparative survey of the presence of viruses in wolves indicated that density and spatial distribution of susceptible hosts, particularly free-ranging dogs, can be important factors influencing infections in wolves (Molnar et al, 2014). However, the assessment of such drivers through comparison of different geographical regions is complicated by lack of data or by the adoption of different approaches, such as necropsy vs coprology (e.g., Guberti et al, 1993; Schurer et al, 2016; Lesniak et al, 2017a, 2017b). Coprology is a non-invasive technique to assess the occurrence of several pathogens (Torres et al, 2001; Kreeger, 2003; Bryan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Each forward and reverse oligonucleotide contained the Fluidigm‐specific common sequence tag CS1 (5′–ACACTGACGACATGGTTCTACA–[TS–For]–3′) or CS2 (5′–TACGGTAGCAGAGACTTGGTCT–[TS–Rev]–3′) to enable subsequent barcoding of the generated PCR products (Fluidigm, San Francisco, CA, USA). PCRs and metabarcoding of Sarcocystis ‐positive sample pools (roe deer: n WT  = 21, n CA  = 10; red deer: n WT  = 10, n CA  = 4; wild boar: n WT  = 20, n CA  = 10) were conducted as previously described (Lesniak, Franz et al., 2017). …”
Section: Methodsmentioning
confidence: 99%
“…(2017). Briefly, OTUs were assigned to Sarcocystis species sequences from a custom database (Lesniak, Franz et al., 2017) using BLAST ® (blastn; Altschul et al., 1990) with an identity threshold of 98%. Only hits with a biunique best bit score for one species were collected in a table including the respective Sarcocystis species, OTU, amplicon, and sample name.…”
Section: Methodsmentioning
confidence: 99%